Facts vs. opinions vs. robots - Rex, Michael (New York : Nancy Paulsen Books, 2020)
Robots try to figure out the difference between facts and opinions.
Kirkus Starred, November 2019
Booklist, December 2019
New York Times, February 2020
School Library Journal, February 2020
1.5
K-3
Keywords: Robots -- Juvenile fiction; Facts (Philosophy) -- Fiction; Opinion (Philosophy) -- Fiction; Robots -- Fiction; Nonfiction picture books